2019
DOI: 10.1007/s11572-019-09516-6
|View full text |Cite
|
Sign up to set email alerts
|

Approaching or Re-thinking the Realm of Criminal Law?

Abstract: In his latest monograph, The Realm of Criminal Law, Antony Duff gives us a further, magisterial statement of the vision of criminal law, its procedural framework, and its sanctioning system, which he has been developing over the past 35 years. This is Duff’s own book-length contribution to the tremendously fruitful collaborative Criminalization project. That project has already generated four edited volumes (Duff et al. in The boundaries of the criminal law, 2010; The structures of the criminal law, 2011; The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…relevant for the present time. This may be proved by several factors of a legal nature related to the trends in the state's criminal policy [10]. This may be a clear desire to reduce the number of people convicted for crimes of small or medium gravity or to avoid further and significant material losses, to weaken criminal repression in certain categories of cases or to increase responsibility for the most dangerous criminal offenses, to increase the opportunities for law enforcers to be relieved of criminal liability or to make wider use of the exemption from punishment, etc.…”
Section: Resultsmentioning
confidence: 99%
“…relevant for the present time. This may be proved by several factors of a legal nature related to the trends in the state's criminal policy [10]. This may be a clear desire to reduce the number of people convicted for crimes of small or medium gravity or to avoid further and significant material losses, to weaken criminal repression in certain categories of cases or to increase responsibility for the most dangerous criminal offenses, to increase the opportunities for law enforcers to be relieved of criminal liability or to make wider use of the exemption from punishment, etc.…”
Section: Resultsmentioning
confidence: 99%
“…All of these areas involve navigating treacherous moral straits in terms of introducing legal sanctions that may disproportionately affect minority communities and imposing majority norms into the private sphere, in addition to raising practical questions as to whether the weight and stigma of hard law are counter-productive when it comes to enabling victims to seek help and protection. Furthermore, where criminal provisions are proposed, there are also links with wider controversies around the impact of criminalisation, as the work of authors such as Lacey (2020) has revealed.…”
Section: Introductionmentioning
confidence: 99%